Designing and evaluating sustainable development pathways for semi‐subsistence crop–livestock systems: lessons from Kenya. (14th November 2017) - Valdivia, Roberto O.; Antle, John M.; Stoorvogel, Jetse J.
Abstract: Achieving the Sustainable Development Goals (SDGs) in African agriculture requires a better understanding why high levels of poverty and resource degradation persist in African agriculture despite decades of policy interventions and development projects. In this article, we hypothesize that policies need to account for the key features of the semi‐subsistence crop–livestock systems (CLS) in the region to become effective. The semi‐subsistence CLS are characterized by a high degree of biophysical and economic heterogeneity and a complex, diversified production system involving a combination of subsistence and cash crops with livestock. We investigated the potential for interventions proposed by the Government of Kenya to meet the SDGs by 2030. The analysis uses an integrated modeling approach designed to deal with the key features of these systems. A strategy that stimulates rural development, increases farm size to a sustainable level, and reduces distortions and inefficiencies in input and output markets could lead to a sustainable development pathway and achieve the SDGs for rural households dependent on CLS.